(untitled) (The Conference Hub, 2025)
The fact that the 22nd goal of the Decree of the President of the Republic of Uzbekistan No. PF-60 dated January 28, 2022 “On the Development Strategy of the New Uzbekistan for 2022-2026” sets out the issue of doubling the volume of textile industry production means that we now need to study and analyze in more depth the scientific foundations of strategic management in the innovative development of the textile industry of Uzbekistan [1].